Implementation of an IoT-Based Energy Consumption Monitoring and Control System for Air Conditioners in Boarding Houses - Aulia, Gading; Mas'udia, Putri Elfa; Wijayanti, Rieke Adriati (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
Electrical energy is a very important basic need in human life. However, the non-renewable natural resources that are often used for power generation can damage the environment. Electricity wastage often occurs due to user negligence. In addition, users often do not have adequate information and tools to properly manage electrical energy consumption. To overcome these problems, this research proposes “Implementation of Monitoring and Controlling System for Electric Power Consumption Based on the Internet of Things (IoT) on Air Conditioner (AC) in Boarding House Environment”. This research aims to reduce the waste of electrical energy by implementing an Internet of Things (IoT) based monitoring and control system on air conditioners (AC) in a boarding house environment. This system uses PZEM004T sensor to monitor electric current and voltage, and Microwave Radar sensor to detect the presence of people in the room. With an Android-based application, users can control and monitor AC power consumption as needed. Based on research that refers to daily energy consumption data of 0.97 kWh, it can be estimated that the energy requirement for 1 week is around ± 29.1 kWh, based on the energy consumption patterns of AC devices that have been identified, users can manage electricity purchases according to estimates and ensure the purchase of electricity. carried out based on actual needs.